Efeito da calagem nas características químicas do solo e no desenvolvimento de mudas de maracujazeiro - (:unkn) unknown (Universidade Federal do Oeste do Pará, 2023)
The development of plants is directly related to the type of treatment they receive, considered as one of the most important, the correction of soil acidity, as it enables the plant to grow more vigorously. The objective of this work was to evaluate the effect of liming on the chemical characteristics of the soil and on the initial development of passion fruit seedlings in western Pará. The experiment was carried out in greenhouse I. The passion fruit cultivar used was BRS Sol do Cerrado, and the yellow latosol soil was collected at Campus Juruti (CJUR/UFOPA). Soil collection was carried out in a 20cm deep layer, for subsequent chemical characterization of pH, Ca, Mg and Al according to the methodology of Embrapa, tomonitor the performance of the limestone application, and subsequently carry out the calculation of the need for liming (NC) and incubation with limestone at 30, 60 and 90 days. The experimental design used was completely randomized (DIC) with six treatments, namely: T1: NC = 100% 30 days of incubation; T2: NC= 100% 60 days of incubation; T3: NC 100% 90 days of incubation; T4: Soil with Organic Fertilizer; T5: pure soil as control; T6: Soil with super liming with 5 replications for each treatment, a total of 30 experimental units. Incubation of limestone to the soil was carried out with a dose calculated according to the Manual of Fertilization and Liming of the State of Pará for the passion fruit crop, applied to the soil 30, 60 and 90 days before transplanting the passion fruit seedlings. Vegetativeparameters were measured during the experiment, such as: Plant height (cm); number of leaves; stem diameter (mm); and after the period of initial development, the seedlings were removed from the pots and the aerial part was separated from the roots and the fresh weight and dry weight of the aerial part (g) were evaluated; fresh weight and dry weight of the root (g); and root volume (ml). Significant results were observed related to the chemical characteristics of the soil for the T6 treatment (Super liming), demonstrating that the dose influenced the Al contents; Here; Mg; H + Al; pH. For the vegetative characteristics of the plant, in all the analyzed variables, the T4 treatment (pure soil and bovine manure) presented better results.
Keywords: Incubação; Maracujá; Acidez do solo; Passiflora edulis; CNPQ:: CIÊNCIAS AGRÁRIAS